IDENTIFIKASI DAERAH JELAJAH RUSA TIMOR (Rusa timorensis) DI TAMAN WISATA ALAM PULAU MENIPO, KECAMATAN AMARASI TIMUR BERBASIS SISTEM INFORMASI GEOGRAFIS - Nixon Rammang; Margareth H. R. Turwewi; Ludji Michael Riwu Kaho; Norman P.L.B. Riwu Kaho (Wana Lestari, 2019)
Deer is a source of animal wealth in Indonesia, consisting of four endemic species, namely: Muntjak Deer (Muntiacus muntjak), Bawean Deer (Axis kuhlii), Sambar Deer (Cervus unicolor), and Timor Deer (Russa timorensis). Timor deer is a species of tropical deeroriginating from Java, often found in various Indonesian archipelago both in its natural habitat and in captivity, management of Timor deer under the Directorate General of Forestry, Nature Conservation and the Ministry of Forestry, its existence is feared to be extinct by the threat of poaching and habitat destruction (Lelono, 2003). The Timor deer (deer timorensis) is one of the most protected wildlife in Indonesia, based on the regulation of the Minister of Environment and Forestry of the Republic of Indonesia number P.106 in 2018 on species of plants and animals Protected, from all forms of hunting, arrest and possession. Field observations are used for two periods, the first period is 06.00 - 10.00 and the second period is 15.00 - 18.00 which is used in data collection for the home range is the Minimum Convex Polygon method and the most commonly used is core utilization or regional data collection, the kernel utilization distribution method. The results showed that the area of deer Timor was scattered in the region, with the area of Timor deer exploration in TWA Menipo Island area of 3425 km2 or 306 hectares (Ha) (12.49% of the total area of TWA Menipo Island) and the core area of 1776 km2 or 170 hectares (Ha) (6.94% of the total area of TWA Menipo Island).